Computer Modeling of the Economy Dynamics of Ukraine, Taking into Account the Socio-Economic Clustering of Society - Buiak, Lesia; Hryhorkiv, Mariia; Hryhorkiv, Vasyl; Bashutska, Oksana; Pryshliak, Kateryna (Journal of Information Technology Management, 2023)
The object of the research is the economic dynamic of a depressed low-productive economy, as exemplified by the modern Ukrainian economy. With the purpose to analyze the main causes and consequences of such an economy, the characteristic tendencies of its functioning, activation of the processes of reformation and growth, there was developed the dynamic economic model with significant share of consumer import and export of raw materials, with the use of IT technology. The model also takes into account the socio-economic clustering of a society. It is formalized in the space of economic variables, which describes respectively the savings (liquid capital) of the main social groups involved in the economy, the prices of 65 Journal of Information Technology Management, 2023, Vol. 15, Issue 4, consumer products in the domestic and foreign markets, the price of exported raw materials for the exchange rate. The model is intended for qualitative analysis of the processes occurring in the economy described by it, and for conducting computational experiments on the basis of information technologies in simulation mode with its parameters, which allows to identify the most characteristic features of the object of the research. The results of experimental researches with the model allowed to establish the main periods of economic dynamics represented by the dynamic variables model, its specificity and social consequences for the society, which is characterized by a bimodal distribution of savings. There was investigation the dependence of the mode solution from it parameters which means in practice the dependence of economic dynamics from the change of individual conditions and factors of economic development. The obtained results are important for informational and analytical support of decision making processes in order to bring the being studied economy out of a low-productive state.
Keywords: Model; Dynamics Equation; Savings, Price; Information Technology; Model Experimental Research